The Impact of Mergers and Acquisitions on the Financial Ratios of Companies Registered with the KPPU - Gunawan, Hendra; Laurenza, Dwi Fitri (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2024)
This study aims to determine the impact of mergers and acquisitions on company financial performance as proxied by liquidity ratios, profitability ratios and efficiency ratios. Data is obtained from financial reports by comparing financial performance ratios before and after mergers and acquisitions. Hypothesis testing uses the Wilcoxon rank test and paired sample t-test. The test results show that there is a significant difference in the liquidity ratio. Meanwhile, profitability ratios and efficiency ratios did not find any significant changes between before and after the merger and acquisition. This study has a limited number of years used to compare financial performance. Future research is expected to use a larger sample of years.